Research progress of Traditional Chinese medicine nursing techniques for constipation in stroke patients (中医护理适宜技术在卒中后便秘患者中的应用进展) - WANG Fang (王芳); GENG Qingwen (耿庆文) (中西医结合护理)
Constipation is a major complication after stroke which seriously affects the quality of life of patients. Traditional Chinese Medicine nursing techniques has been widely used in clinical practice in recent years. This paper reviewed the studies on Traditional Chinese medicine nursing techniques including moxibustion, auricular acupoint pressing, acupoint application and abdominal massage in treating post-stroke constipation, and provided reference for clinical practice of constipation management in stroke patients. (便秘是脑卒中患者常见并发症, 严重影响患者生活质量。中医护理适宜技术在临床中应用广泛, 效果明确, 且患者接受度较高。本研究就中医护理适宜技术灸法、耳穴贴压、穴位贴敷、腹部推拿等多项技术在卒中后便秘患者护理中的应用状况进行综述, 旨在为脑卒中后便秘的临床实践提高参考依据。)